DISTANCE LEARNING MATHEMATICS USING PQ4R LEARNING STRATEGIES (PREVIEW, QUESTION, READ, REFLECT, RECITE AND REVIEW) - Sutini Sutini; Lisanul Uswah Sadieda; Rohmatul Ummah; Azmi Wanda Muryta (IAIN Ambon, 2022)
The Covid-19 pandemic that has hit Indonesia poses a challenge for educators to find effective and efficient alternatives to distance learning. Therefore, this study aims to develop distance math learning devices using the PQ4R (Preview, Question, Read, Reflect, Recite and Review) learning strategies that are valid, practical and effective. This type of research is development research that uses the Plomp development model. This research was conducted at SMPN 1 Duduksampeyan Gresik in the 2021/2022 academic year. The learning devices developed consist of lesson plans and worksheet on the set material.The development phase consists of an initial investigation phase, a design phase, a realization or construction phase and a test, evaluation and revision phase. Data collection methods used are tests, observations and questionnaires. The data were analyzed using the formula for the average value and the percentage was then classified according to the established criteria. The results of data analysis show that distance math learning devices using the PQ4R learning strategies are in the valid, practical and effective categories. This can be seen from the average validity of the lesson plan and student worksheet of 3.78 and 3.87, respectively. While the average practicality of lesson plan and student worksheet are 3.93 and 3.92, respectively. The implementation of the syntax of learning mathematics is included in the very good category with a percentage of 100%. The response of students after participating in the lesson was very positive. Student learning outcomes are included in the very good category with a percentage of completeness of 90.63%.